Bridgerton: it's in his kiss - Quinn, Julia (London Piatkus (Hachatte India), 2005)
'A veritable treat' Daily MailThe seventh novel in Julia Quinn's globally beloved and bestselling Bridgerton Family series, set in Regency times and now a series created by Shondaland for Netflix. This is Hyacinth's story: she's all grown up and ready to cause havoc . . .________________________________________All the ton agree: there is no one quite like Hyacinth Bridgerton. Fiendishly smart, devilishly outspoken and - according to some, particularly Gareth St. Clair - probably best in small doses. But there's something about her - something charming and vexing - that grabs one and won't quite let go. Gareth and Hyacinth cross paths at the annual - and annually discordant - Smythe-Smith musicale. To Hyacinth, Gareth's every word seems a dare, and she offers to help him out with a knotty inheritance problem he's facing. However, as they delve into the mysterious St Clair history, they discover that the answers they seek lie not in the past - but in each other; and that there is nothing as simple - or as complicated - as a single, perfect kiss.Find out why readers love Julia Quinn . . .'Light, pacy and full of feisty heroines' Guardian on the Bridgerton series'Julia Quinn's Bridgerton books take all of the classic tropes we know and love . . . and gives them a thoroughly modern twist. I can't focus on anything else' Stylist'Quinn is a master of historical romance' Entertainment Weekly'A smart, funny touch' Time Magazine'Like an episode of Downton Abbey mixed with a great rom-com' iBooks Best Books of March'Powered by a surfeit of dazzling wit and graced with a cast of unforgettable characters' Booklist'A romance readers will not want to put down . . . Hooray Julia!' Romance Reviews Today'Quinn writes delightfully fast-paced, funny, sparkling and bright romance' Romantic Times'The next best thing to Georgette Heyer' Gloss'Julia Quinn is one of the best historical romance novelists of our time' Heroes and Heartbreakers'Quinn excels in writing stories full of joy and delight, where laughter trembles on the edges' Happy Ever After'Full of wit, charm and smouldering attraction . . . an unputdownable story that I think romance fans will treasure' Harlequin Junkie'Quinn is incomparable! The latest addition to her beloved Bridgerton series is funny, charming, witty and wildly romantic' RT Book Reviews
Keywords: Fiction- English; Histirical Fiction